Electromyography (EMG) analysis for pre-clinical trials of hand rehabilitation tasks - Ang, Kok Yong (2009)
With the prevailing demand for medical care due to the graying population, there is a greater need for healthcare professionals like therapists, both physical and occupational. This project aims to integrate bio-signals, that is, electromyography (EMG) signals, with a hand rehabilitation device which serves as a tool in the therapists’ work of planning, assessing and intervention with patients. The three-tier approach implemented includes an in-depth assessment on hand motions, development of pre-clinical grading system and a comprehensive study on correlation of force and EMG signals. Primarily, the present study focuses on capturing the EMG signals for five activities for daily living (ADL) tasks – five-pulp pinch, lateral pinch, pulp-to-pulp pinch, tripod grip and cylindrical grip. The testing conducted on twenty-five subjects ranged from seventeen to seventy-eight years old. Prior to the subject testing, experimental results of specific hand motions had provided a platform for the understanding of extrinsic and intrinsic muscles and the selection muscle groups. Furthermore, the usage of fractional and factorial design of experiments, ANOVA and the least significant difference level test (t-test) has shown that age is a predominant factor attributing to the difference in EMG signals and force. Also, the age group between 45 to 59 years old is found to have little difference with the age group 60 years old or greater, but the age group, less than 45 years old, is different from the two senior age groups. Therefore, this leads to the derivation of the pre-clinical grading system for hand rehabilitation for post-stroke and spinal cord injury (SCI) patients. Lastly, to incorporate the above findings with the design domain of the hand rehabilitation device research, the relationship between force and EMG signals is further explored. The study of passive and active forces has reflected that the latter has significantly higher EMG signals comparatively. The flexion angle of fingers, position of actuator (at tip end of PIP joint) and materials of contact have shown to have an effect on the amount of force exerted too.